Faktor-faktor yang Berhubungan dengan Perilaku Keselamatan Berkendara (Safety Riding) pada Mahasiswa STIKES Persada Husada Indonesia - Lean, Irene Santia Putri; Agustina, Agustina; Herlina, Herlina (Jurnal Persada Husada Indonesia, 2024)
A traffic accident is an undesirable event that occurs on the road unexpectedly and unintentionally. Safety riding is a method used to reduce traffic accidents. Behavior is a person's activity or activity. The aim of the research is to determine the factors related to safe riding behavior among STIKES PHI students. This type of research uses quantitative methods with a cross-sectional approach, the research was conducted at STIKES PHI with a population of all STIKES PHI students who can ride motorbikes. The number of samples calculated using the Tarro Yamane formula was taken as many as 58 students, using a purposive sampling technique. The analysis used was univariate analysis and bivariate analysis with the chi-square test. Based on the results of univariate analysis, of the predisposing factors in the female gender category, there were 40 people (69%), the highest knowledge was low knowledge, 37 people (63.8%), the most positive attitude was 32 people (55.2%). Of the reinforcing factors for the family support category, 37 people (63.8%) had less family support (63.8%), less safe behavior was 32 people (55.2%). The results of the bivariate analysis research show that there is a significant relationship between knowledge with a p-value of 0.002 (<0.05), attitude with a p-value of 0.000 (<0.05). It is hoped that counseling regarding safe riding can be held on campus to increase knowledge and attitudes about safe riding.